Blended Learning dalam Pengajaran Bahasa Arab: Kolaborasi Antara Guru Tersertifikasi - Musonif, Mohammad Zaelani; Kusumadewi, Novita; Ahsanuddin, Mohammad (Arabi : Journal of Arabic Studies, 2023)
The purpose of writing this article is to describe the learning components at PUSIBA, analyze the implementation of the blended learning model in Arabic language learning at PUSIBA, examine further the collaboration carried out by sheikh from Egypt and PUSIBA, and analyze the achievement of aspects of the blended learning model in learning at PUSIBA. The research method used is a descriptive qualitative method with a phenomenological approach. The research results obtained were (1) the curriculum and learning materials at PUSIBA follow the Markaz Syaikh Zayed curriculum in Egypt by adjusting the existing levels of learning and accommodating the teaching of the four language skills, listening, speaking, reading, and writing, (2) the learning process in PUSIBA is carried out in blended learning for five months with the sheikh from Egypt and also teachers who have completed Arabic language teaching training from Markaz Syaikh Zayed, and (3) learning collaboration between sheikh from Egypt and PUSIBA is carried out online and offline, and (4) Arabic learning at PUSIBA fulfills five aspects of the blended learning model, live events, self-paced learning, collaboration, assessment, and performance support materials.